The relationship between body mass index (BMI) and agility of UKM futsal players UPI Sumedang campus - Vianka, Nukeu; Salsabila, Dinda Astiana; Firdaus, Natasya Nurlaila; Suherman, Ayi; Rahman, Aam Ali (Jurnal Ilmu Keolahragaan, 2024)
This study aims to analyze the relationship between Body Mass Index (BMI) and agility of futsal players in UKM Futsal UPI Sumedang Campus. The method used was quantitative with a correlational design, involving 30 student members of UKM Futsal with an age range of 19-21 years. Data were collected through questionnaires to measure BMI and agility tests using the zig-zag and shuttle run methods. The results showed that there is a significant relationship between BMI and agility, where players with more ideal BMI tend to have better agility. In addition, this study also found that physical conditions, especially agility and technical skills, are very important in the game of futsal. The training done by university students, which averages 2-3 times per week, is still low compared to the recommendations for competitive athletes. Therefore, an increase in training frequency and attention to diet is highly recommended to support athlete performance. This study provides important insights for futsal coaches and players in designing more effective training programs, as well as emphasizing the importance of maintaining a healthy BMI to improve agility and performance in the game. The results of this study are expected to be a reference for further research in the field of sports, especially futsal, and contribute to the development of better quality athletes.